2005
DOI: 10.1038/sj.leu.2403938
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of microRNA-125b-1, a human homologue of lin-4, into a rearranged immunoglobulin heavy chain gene locus in a patient with precursor B-cell acute lymphoblastic leukemia

Abstract: Insertion of microRNA-125b-1, a human homologue of lin-4, into a rearranged immunoglobulin heavy chain gene locus in a patient with precursor B-cell acute lymphoblastic leukemia Leukemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 8 publications
2
83
0
3
Order By: Relevance
“…7 RT-PCR using primers set at VH and Cm produced two PCR products (390 and B170 bp). (c) Relative expression levels of miR125b were examined by real-time PCR in 293T cells transduced with pMXsEF1-IGH/miR-125b-1-(GFP), miR-125b expression vector (pMXsEF1-miR-125b-(GFP)) or mock (pMXsEF1-(GFP)).…”
Section: Mir125bmentioning
confidence: 99%
See 3 more Smart Citations
“…7 RT-PCR using primers set at VH and Cm produced two PCR products (390 and B170 bp). (c) Relative expression levels of miR125b were examined by real-time PCR in 293T cells transduced with pMXsEF1-IGH/miR-125b-1-(GFP), miR-125b expression vector (pMXsEF1-miR-125b-(GFP)) or mock (pMXsEF1-(GFP)).…”
Section: Mir125bmentioning
confidence: 99%
“…A miRNA expression cassette was constructed in the opposite direction from a GFP expression cassette. Expression fragments of miR-125b or IGH/ miR-125b-1 were PCR amplified from C57BL/6 mouse genomic DNA or cDNA of tumor derived from a BCP-ALL patient, 7 respectively. Primer pairs are described in 'Supplementary Materials and methods'.…”
Section: Vector Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs can function as tumor suppressors or oncogenes, depending on their specific target genes (6,7). For example, miR-145, miR-335, miR-125b-1, miR-126, miR-15a, miR-16-1, miR-31, and miR-335 are all tumor suppressors for specific cancer types (8)(9)(10)(11). Recent studies have shown that miRNAs are involved in the malignant progression of breast cancer (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%